Impact of Microfinance Programmes on Information and Political Empowerment of Women in Nepal - Duwal, Bal Ram (Bagiswori Journal, 2019)
The study covers the impact of microfinance programmes on information and political empowerment of participants located in Dhulikkhel Municipality. 60 women members were selected for the study using judgmental sampling method. Descriptive and explanatory research design has been adopted to fulfil the objectives of the study. The present study concludes that the MFIs are focusing more on saving and lending practices but they have failed to give serious attention towards effective training and insurance services. Microfinance members perceived political empowerment through microfinance programme. However, they pointed out the impact of microfinance programme on information empowerment to some extent. Further, microfinance services and women information empowerment has significant relationship but there is no significant relationship between microfinance services and women political empowerment. It is visualized that marital status and source of income of respondents show difference on political empowerment only. For political empowerment, MFIs need to operate various information sharing activities, training based on income generation and social mobilization. As being grassroots level institutions, MFIs need to focus on capacity enhancement of women for political lead too.